DOOM SPENDING AMONG GENERATION Z: AN ANALYSIS OF IMPULSIVE BUYING BEHAVIOR ON E-COMMERCE PLATFORMS - Andrean, Rizky; Fikri, Muhammad Khoirul; Wulan, Elis Ratna (UIN Raden Mas Said Surakarta, 2025)
The development of digital technology and the rapid use of e-commerce platforms have driven changes in consumption behavior, especially among Generation Z. One of the emerging phenomena is doom spending, which refers to consumption driven by emotional pressure or stress. This study aims to examine the effect of hedonic shopping motivation, social influence, and perceived ease of use of e-commerce platforms on impulsive buying among Generation Z. This research employed a quantitative method with a purposive sampling technique, involving 269 respondents. Data were analyzed using SEM-PLS with SmartPLS 3. The findings indicate that hedonic shopping motivation and social influence exert a positive and significant effect on impulsive buying, whereas perceived ease of use does not significantly affect impulsive buying behavior. These results highlight that emotional gratification and social pressures are the primary triggers of impulsive buying among Generation Z rather than the perceived simplicity of the platform. This study contributes to the growing discourse on digital consumer behavior by providing empirical evidence on the drivers of doom spending in the Indonesian Gen Z context, offering insights that can inform e-commerce platform strategies and consumer well-being interventions